Pengaruh Penambahan Tepung Buah Mengkudu (Morinda Citrifolia) dalam Pakan terhadap Performans dan Gambaran Darah Ayam Jantan Pedaging - Ruswandono Wirjatmadja (VITEK : Bidang Kedokteran Hewan, 2015)
The purpose of this research is to know the influence of the addition of flour mengkudu in performans on feed on blood profile male broiler. This study using 24 male broiler reared from doc until 2 weeks old , after 2 weeks old the chicken divided randomly in 4 of the treatment as follows. ( po ) groups of chickens without treatment , done four times test . ( p1 ) groups of chickens by the addition of flour mengkudu into feed as many as 5 % ( p2 ) groups of chickens by the addition of flour mengkudu in feed to ten percent . ( p3 ) groups of chickens by the addition of flour mengkudu to in feed fifteen percent. The provision of feed has been given additional flour mengkudu done three times in one day , in the morning , afternoon , and night . After 42 days chicken harvested and weighed the increase of weight , consumption of feed and taken blood samples for laboratory. Data from the results of research on a male broiler given additional flour mengkudu in feed to a draft design experiment completely random and data analyzed by the method of analysis of variant ( ANOVA ).The results of research , it can be concluded that the addition of flour fruit mengkudu in feed male broiler cattle by 5 percent : 10 percent and 15 percent , do not affect the consumption of feed , body weight , the conversion of fodder and the number of the number of erythrocytes and leukocytes